Diversity of rodents and shrews along an elevational gradient in Bwindi Impenetrable National Park, south-western Uganda - Kasangaki, Aventino; Kityo, Robert; Kerbis, Julian (African Journal of Ecology, 2003)
Small mammal species diversity in the major vegetation zones of Bwindi Impenetrable National Park is discussed in relation to altitude. Species richness of the smallmammals was found to decrease with an increase in altitude. The main factors accounting for the observed diversity are the wide altitudinal variation and a complex array of vegetation types. Sixty-seven species of rodents and shrews were found to exist in the Park; 47 of which were rodents and 20 shrews. Of these, 26 species are new to theBwindi Park list.Three species have probably notbeen described before. The study found 10 species of small mammals to be Albertine Rift endemics. Three genera are recorded in Uganda for the ¢rst time: Rwenzorisorex, Suncus and Paracrocidura. Five species are new records for East Africa. These are Crocidura stenocephala, Lophuromys rahmi, L. medicaudatus, Paracrocidura maxima and Hylomyscus aeta. Because of thehigh endemismof plants, butter£ies, birds and now of small mammal species, Bwindi forest is a unique biodiversity hotspot and is among the highest conservation priorities in the Albertine Rift.
Keywords: Altitude; Bwindi impenetrable; Endemism; Rodents; Shrews